A Recessive Resistance to Rice yellow mottle virus Is Associated with a Rice Homolog of the CPR5 Gene, a Regulator of Active Defense Mechanisms - Orjuela, J.; Deless, E.F.T.; Kolade, O.; Chéron, S.; Ghesquière, A.; Albar, L. (Scientific Societies, 2013)
RYMV2 is a major recessive resistance gene identified in cultivated African rice (Oryza glaberrima) which confers high resistance to the Rice yellow mottle virus (RYMV). We mapped RYMV2 in an approximately 30-kb interval in which four genes have been annotated. Sequencing of the candidate region in the resistant Tog7291 accession revealed a single mutation affecting a predicted gene, as compared with the RYMV-susceptible O. glaberrima CG14 reference sequence. This mutation was found to be a one-base deletion leading to a truncated and probably nonfunctional protein. It affected a gene homologous to the Arabidopsis thaliana CPR5 gene, known to be a defense mechanism regulator. Only seven O. glaberrima accessions showing this deletion were identified in a collection consisting of 417 accessions from three rice species. All seven accessions were resistant to RYMV, which is an additional argument in favor of the involvement of the deletion in resistance. In addition, fine mapping of a resistance quantitative trait locus in O. sativa advanced backcrossed lines pinpointed a 151-kb interval containing RYMV2, suggesting that allelic variants of the same gene may control both high and partial resistance.